Cycle-to-Cycle Variations of a Diesel Engine Operating with Palm Biodiesel - R., Mamat; Abdul Adam, Abdullah; Mohd Hafizil, Mat Yasin; Nik Rosli, Abdullah; Wyszynski, Miroslaw L. (2013)
Biodiesel is one of biodegradable and renewable fuel which is originated from vegetable oil or animal fats. Different fuel properties of biodiesel produce different combustion characteristics which slightly differ to mineral diesel. Combustion studies on palm-biodiesel and mineral diesel were conducted using a multi-cylinder diesel engine. Cycle-to-cycle variations of peak cylinder pressure and mean indicated pressure of the test fuels were determined for the combustion characteristics of diesel engine. In-cylinder pressure data for the 200 consecutive cycles were determined using a Kistler pressure transducer and recorded into a combustion analyzer. Three different engine loads: 20%, 40% and 60% were selected in this study with a constant engine speed of 2500 rpm. The results show that at lower load, in-cylinder pressure variations for palm biodiesel were lower compared to mineral diesel. However at medium and high loads, palm biodiesel has dominated the peak cylinder variations.